1996
DOI: 10.1111/j.1600-0609.1996.tb00495.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 1 receptor antagonist (IL1RA) in acute leukaemia: IL1RA is both secreted spontaneously by myelogenous leukaemia blasts and is a part of the acute phase reaction in patients with chemotherapy‐ induced leucopenia

Abstract: Blast cells derived from peripheral blood of patients with acute myelogenous leukaemia (AML) were cultured in vitro and interleukin 1 receptor antagonist (IL1RA) concentrations determined in culture supernatants. AML blasts derived from patients classified as AML‐M4 and AML‐M5 subtype showed an increased release of IL1RA. IL1α and IL1β caused a similar increase in AML blast release of IL1RA, and addition of anti‐ILl antibodies decreased IL1RA release. IL1RA release from AML blasts was also increased by stem ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
(40 reference statements)
2
6
0
Order By: Relevance
“…IL-1RA is secreted spontaneously by AML cells [67] and its major function is to competitively inhibit receptor binding of IL-1 that has been shown to play a role in AML proliferation. Addition of IL-1RA to cell cultures has been shown to decrease AML colony formation [68], but the concentrations used in this study were much higher than those concentrations found in our long-term cultures.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1RA is secreted spontaneously by AML cells [67] and its major function is to competitively inhibit receptor binding of IL-1 that has been shown to play a role in AML proliferation. Addition of IL-1RA to cell cultures has been shown to decrease AML colony formation [68], but the concentrations used in this study were much higher than those concentrations found in our long-term cultures.…”
Section: Discussionmentioning
confidence: 99%
“…The cytokine-cluster analysis showed several alterations during treatment, an observation suggesting this treatment alters the cytokine network. Several of the cytokines included in the present analyses have effects on primary human AML cells [30,[42][43][44][45], and the altered cytokine network may thereby directly affect the AML cells and also have immunomodulatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Here, IL-1RA levels were increased in sera from CRMO patients when compared to healthy controls, indirectly indicating increased inflammasome activation and IL-1β release. The post-translational regulator IL-1RA, however, directly reflects IL-1β release and may therefore be used as an indirect marker for IL-1β secretion ( 13 ). In a previous study ( 10 ), serum IL-1RA was not different between CRMO patients, JIA patients and healthy individuals.…”
Section: Discussionmentioning
confidence: 99%